Peningkatan Pemahaman Masyarakat dalam Membangun Konservasi Mangrove di Segara Anakan Cilacap - Endang Hilmi; Norman Arie Prayogo; Teuku Junaidi; Arif Mahdiana; Rose Dewi; Lovine Khoirunisa (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Communities in the Segara Anakan Lagoon area of Cilacap still do not firmly understand the services of mangrove ecosystems and the impacts that will occur due to the loss and destruction of mangrove ecosystems for people's lives, the sustainability of community economic activities, and the existence of habitat organisms in Segara Anakan. For this reason, it is necessary to conduct socialisation activities on the importance of mangrove ecosystems to maintain their ecosystem services through mangrove conservation activities. This activity was attended by fishermen, stakeholders, boat drivers, kerrang collectors, pond farmers, nipah craftsmen, nifah sugar makers, and so on. The socialisation resulted in an increased understanding of the importance of mangroves, mangrove ecosystem services, and the impacts that will occur if mangroves are damaged. For this reason, the community is also willing to conserve and rehabilitate mangrove ecosystems in Segara Anakan.